First record of Piscicapillaria bursata (Nematoda: Capillariidae), a parasite of hammerhead sharks Sphyrna spp., in the western Atlantic Ocean - Moravec, František; Dalrymple, Kaitlyn M; Galloway, Ashley S; Barker, Amanda M; de Buron, Isaure (Diseases of aquatic organisms, 2020)
Examination of 32 spiral valves from neonate specimens of hammerhead shark Sphyrna spp. (Carcharhiniformes: Sphyrnidae) captured between June and August 2018 off the Atlantic coast of South Carolina, USA, revealed the presence of the capillariid nematode Piscicapillaria bursata (Capillariidae) in the Carolina hammerhead S. gilberti, the scalloped hammerhead S. lewini, and their hybrids. This is the second find of this parasite originally described from hammerhead sharks off Australia, its first record from the western Atlantic Ocean, and its first record in a new host species and in hybrids.
Keywords: Sphyrnidae; Parasitic nematode; Austrálie; Atlantský oceán; Jižní Karolína; Animals; Australia; USA; Nematoda; South Carolina; Sharks; zvířata; hlístice; Atlantic Ocean; Trichinelloidea; žraloci